Electrochemical methods for determining diffusion coefficient of hydrogen in steels. (May 2015) - Fumagalli, G.; Bolzoni, F.; Fallahmohammadi, E.; Re, G.; Lazzari, L.
<x content-type="archive" xml:space="preserve">Abstract</x> Transport of atomic hydrogen in steels can be described by a complex model that takes into account diffusion laws (Fick's laws) and the phenomena of hydrogen capture and release by different traps. Different electrochemical methods for measuring the diffusion coefficient of atomic hydrogen are compared. Three metallurgical structures of low alloy 2·25Cr–1Mo steel and C–Mn microalloyed steel are tested, the latter also with different degrees of plastic deformation. The test methodology that best simulates hydrogen diffusion through a lattice is the partial charge/discharge method. Within the limits of the 'material–environment' combinations selected for this research, highly reproducible values of the diffusion coefficient are obtained, which decrease in the order of annealed (10− 9 m2 s− 1), quenched and tempered (5 × 10− 10 m2 s− 1) and quenched (10− 10 m2 s− 1) samples and also decrease as the plastic deformation increases (from 5 × 10− 10 to 5 × 10− 11 m2 s− 1).